Optimal sizing and technical assessment of a hybrid renewable energy solution for off-grid community center power - Tamoor, Muhammad; Bhatti, Abdul Rauf; Hussain, Muhammad Imtiaz; Miran, Sajjad; Kiren, Tayybah; Ali, Asma; Lee, Gwi Hyun (Frontiers in Energy Research, 2023)
Decentralized energy generation systems based on renewable sources have significant potential to assist in the sustainable development of developing countries. The small-scale integration of hybrid renewable energy systems in off-grid communities has not been thoroughly researched. The primary objective is to develop a preliminary design for a PV/biogas hybrid system that can meet the energy needs of an off-grid community center. A survey was conducted to calculate the energy demands of an off-grid community center and a hybrid renewable system has been designed to supply the electricity. The optimum designed system is evaluated by the PVSYST simulation software and SuperPro Designer software. The annual production of the PV system is 34428 kWh/year, specific production is 1118 kWh/kWp/year, and the performance ratio is 81.72%. All the factors that contribute to energy loss are considered in designing a PV system. The average operating efficiency of the inverter is 92.6%, and global inverter losses are 2752.4 kWh. The biogas simulation findings show an adequate match with the composition of conventional biogas and contains 89.64% methane and 5.99% carbon dioxide content. Two sensitivity analyses of biogas based on hydraulic retention time and moisture content have been performed. Measurements readings of hourly data are used to analyse the performance of PV, biogas system as well as the hybrid system performance. At day time, the maximum power generation of the hybrid PV/Biogas and the maximum load demand of the community at that time are 25.2 kW and 24.31 kW, respectively. At night time, the maximum power generation of the hybrid system and the maximum load demand are 9 kW and 8.3 kW, respectively. The power factor (PF) of the system fluctuates between 0.92 and 0.98 and the frequency of the system is constant at 50 HZ.